Sistem Informasi Madrasah Diniyah Takmiliyah Awaliyah Nurul Ikhlas Babakan Tipar Kabupaten Sukabumi - Sulaiman, Hamdun; Panggalih, Kukuh; Yuliani, Yuri; Iqbal Alifudin, M. (Jurnal Sistem Informasi Akuntansi, 2024)
The application of information technology in education is very important to increase the efficiency and effectiveness of administrative processes. This research aims to design and develop an information system for Madrasah Diniyah Takmiliyah Awaliyah Nurul Ikhlas Babakan Tipar, Sukabumi Regency. This system is designed to provide information regarding school profiles, management data, activity news, agendas, announcements, and activity documentation. With this website-based information system, schools can convey information more effectively and efficiently, as well as increase interaction and communication with the community. This research uses a system development method that involves needs analysis, system design, implementation, and testing. The research results show that the designed website can increase the accessibility of school information, facilitate communication between the school and the community, and support information transparency. Apart from that, this website is also expected to improve the school's image in the eyes of the public and become an effective promotional media.